Gaussian Beam Migration for Free-Surface Multiples in VSP - Yu, Dai; Yang, Feilong; Wen, Bo; Wang, Ying; Huang, Dezhi; Zhao, Chi (Frontiers in Earth Science, 2022)
The Vertical Seismic Profiling (VSP) Gaussian beam migration is a seismic imaging method with both computational efficiency and imaging precision. It can get high-resolution structural features near the well. However, the VSP migration based on primary reflections imaging is limited by the observation system, which makes it unable to image for the shallow structure at far offset. The free-surface multiples in VSP can expand the illumination range for far offset effectively. Therefore, Gaussian beam migration (GBM) for free-surface multiples imaging in VSP is proposed. Firstly, based on the ground Gaussian beam pre-stack depth migration, the method for decomposing the plane wave is improved and adapted into VSP geometry. We decompose the seismic records received by the well into plane waves in different directions according to different window centers, and image the plane wave of each direction independently. Secondly, through the mirror image of both velocity model and VSP receivers, the VSP free-surface multiples are converted into VSP primary reflections which are involved in the VSP Gaussian beam migration method, and thus the method of the primaries is used to image the free-surface multiples. Finally, the effectiveness and robustness of the proposed method are verified by theoretical model and practical data.